2015
DOI: 10.3389/fphar.2015.00074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of murine exposure to gamma rays on the interplay between Th1 and Th2 lymphocytes

Abstract: Gamma radiation radiotherapy is one of the widely used treatments for cancer. There is an accumulating evidence that adaptive immunity is significantly contributes to the efficacy of radiotherapy. This study is carried out to investigate the effect of gamma rays on the interplay between Th1/Th2 response, splenocyte lymphoproliferative response to polyclonal mitogenic activators and lymphocytic capacity to produce IL-12 and IL-10 in mice. Results showed that exposure of intact spleens to different doses of γ-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…PD also suppressed upregulation of TGFβ‐Smad3 signalling pathway and epithelial–mesenchymal transition, which was reported playing critical roles in lung fibrosis . Irradiation of lung tissues also caused a dysregulation of cytokines, exhibiting upregulation of inflammatory cytokines and shift of Th1/Th2 immunity . Our data showed that PD inhibited radiation‐induced inflammation and Th1/Th2 imbalance.…”
Section: Discussionsupporting
confidence: 59%
“…PD also suppressed upregulation of TGFβ‐Smad3 signalling pathway and epithelial–mesenchymal transition, which was reported playing critical roles in lung fibrosis . Irradiation of lung tissues also caused a dysregulation of cytokines, exhibiting upregulation of inflammatory cytokines and shift of Th1/Th2 immunity . Our data showed that PD inhibited radiation‐induced inflammation and Th1/Th2 imbalance.…”
Section: Discussionsupporting
confidence: 59%
“…The expression and regulation of IL-12, a pro-inflammatory and Th 1 immune response regulatory cytokine, is directly proportional to IFNg. 5,11,19,21 Irradiated macrophages showed suppression of IL-12 levels at all tested time-points (except 2 hours; Figure 5E). Moreover, previous reports have indicated that dwindling IL-12 levels cause declined stimulation of IFN-g by Th 1 cells.…”
Section: Ifn-g Is Secreted From Macrophages and Activates Cytotoxic Tmentioning
confidence: 95%
“…Th 1 immune response is aided by IL‐2, IL‐12, TNF‐α, and interferon‐γ (IFN‐γ) cytokines. While, Th 2 immune response is primarily generated by IL‐4, IL‐5, IL‐6, IL‐9, IL‐10, IL‐13, and IL‐17E cytokines …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Th1/Th2 cytokines equilibrium was evaluated based on the level of IFN-γ/IL-4, from which the Th1/Th2 cytokines ratio was calculated. 18 , 19 The secondary endpoint was the VAS pain scores, which were measured at predetermined intervals (0, 12, 24 and 48 h) after surgery. If the patient-reported VAS score was ≥4, the analgesic pump was first pressed to add drugs, then the patient was re-evaluated after 15 min.…”
Section: Methodsmentioning
confidence: 99%